Ugandan School Children Contributing to the Health of their Nation - International Potato Center (2018)
In Uganda, between June 2015 and July 2018, the International Potato Center (CIP) worked with the National Curriculum Development Centre (NCDC) in the Ministry of Education and Sports (MoES) to develop four supplementary readers with orange-fleshed sweetpotatoes as a major theme for primary school children. These were introduced successfully into 56 schools in Uganda.